Families, public policies, and the labor market - Gordon B. Dahl; Katrine V. Løken (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Over the past two decades, there have been significant changes in family dynamics and labor market interactions, with shifts in fertility, marriage, divorce, cohabitation, family labor supply, gender inequality, and childrearing. This chapter examines the impact of government policies on these trends, highlighting the latest research across different OECD countries. The best evidence comes from administrative data and modern econometric methods. The chapter concludes with a summary of lessons learned and directions for future research.
Keywords: 330; Family; Labor market; Family policy; Labor market policy; OECD countries; Familie; Arbeitsmarkt; Familienpolitik; Arbeitsmarktpolitik; OECD-Staaten